The Influence of Depressive Symptoms on Suicidal Ideation Among U.S. Vietnam-Era and Afghanistan/Iraq-Era Veterans With Posttraumatic Stress Disorder - Pukay-Martin, Nicole D. (2012)
Major depressive disorder (MDD) co-occurs frequently with posttraumatic stress disorder (PTSD), and both disorders are linked to suicidal ideation. An emergent literature examines suicidal ideation in U.S. Afghanistan/Iraq-era veterans. Little research, however, has studied the role of PTSD and comorbid MDD on suicidal ideation across service eras. Therefore, this study aimed to examine the impact of depression on suicidal ideation in Afghanistan/Iraq-era and Vietnam-era veterans with PTSD. The sample included 164 Vietnam and 98 Afghanistan/Iraq veterans diagnosed with PTSD at a VA outpatient PTSD Clinic. Using structured interviews, 63% of the Vietnam sample and 45% of the Afghanistan/Iraq sample were diagnosed with comorbid current MDD. Measures included self-report assessments of PTSD and depressive symptoms and the Personality Assessment Inventory. Results of analyses suggested that in veterans of both eras, PTSD, MDD, and their interaction were significantly related to suicidal ideation (PTSD: η(2) = .01; MDD: η(2) = .10; PTSD × MDD: η(2) = .02). For veterans reporting greater depressive symptoms, there was a stronger relationship between PTSD symptoms and suicidal ideation. These results suggest that veterans from both eras display a similar clinical presentation and highlight the need to consider depressive symptoms when assessing veterans with PTSD. Future research should examine suicidal ideation and behaviors as they change over time in these two cohorts.